Polyethylene Glycol-grafted poly alpha-lipoic acid-dexamethasone nanoparticles for osteoarthritis - Cheng, Yuanqiang; Jing, Zheng; Xu, Yan; Sun, Lihui; Li, Dongbo; Liu, Jianguo; Li, Dongsong (Frontiers in Drug Delivery, 2023)
Osteoarthritis (OA) is a chronic inflammatory disease that causes synovial hyperplasia, cartilage destruction, and the formation of bone spurs. Macrophages play an indispensable role in the pathogenesis of OA by producing proinflammatory cytokines. To achieve the effect of arthritis, hormones can effectively inhibit the progression of inflammation by inhibiting the secretion of inflammatory cytokines by macrophages in traditional therapy. However, the drug is quickly cleared from the joint space, and the high injection site infection rate and low local drug concentration make the clinical efficacy of corticosteroids greatly reduced. We described the design and preparation of Polyethylene Glycol-grafted Poly Alpha-lipoic Acid-dexamethasone Nanoparticles (NPDXM/PPLA), elucidated the mechanism of action of NPDXM/PPLA in the treatment of OA in mice, and provided an experimental basis for investigating the treatment of OA with polymer nanoparticles loaded with dexamethasone. Flow cytometry and confocal laser scanning microscopy were used to confirm that NPDXM/PPLA was well absorbed and released by macrophages, and it was discovered that NPDXM/PPLA could efficiently reduce the proliferation of activated macrophages (RAW 264.7 cells). Enzyme-linked immunosorbent assay revealed that NPDXM/PPLA could efficiently reduce the expression of proinflammatory cytokines IL-1β, IL-6, and TNF-α. The knee bone structure of OA mice was investigated by MicroCT, and it was discovered that intraarticular injection of NPDXM/PPLA effectively alleviated the bone damage of the articular cartilage. Therefore, NPDXM/PPLA is a potential therapeutic nanomedicine for the treatment of OA.